Itäsaamelaiskielten partitiivi kielioppien mukaan sekä korpushavaintoja inarin- ja koltansaamesta - Koivunen Tomi (Debreceni Egyetemi Kiadó, 2025)
Partitive of the Eastern Saami languages according to grammars,
with corpus observations of Aanaar and Skolt Saami
The article deals with the partitive case of the Eastern Saami languages,
namely Aanaar (Inari), Skolt, Akkala, Kildin, and Ter Saami. The case is
called partitive, because its form is etymologically of the same origin as the
Finnic partitive. In Saami languages, however, its field of use is much narrower,
as it is only used with some quantifiers and also as a complement to
certain adpositions and numerals and to express the standard of comparison.
The article discusses how the grammars of different Eastern Saami languages
describe the use of the partitive. In addition, the article analyzes Aanaar and
Skolt Saami more deeply based on the corpus material.
By comparing grammars and materials, it becomes clear that the partitive
is used in different Eastern Saami languages basically in the same way, but
there are also some differences between individual languages. The biggest
differences concern the use of the partitive in connection with adpositions
and quantifiers. Regarding Aanaar and Skolt Saami, the study also shows
that the descriptions given by grammars about the use of the partitive do not
fully correspond to actual language use. There also seem to be some misinterpretations
in the grammars, especially at the eastern end of the language
continuum.